Factors That Influence Entrepreneur Success In City Of Medan - Selwendri Selwendri; Onan Marakali Siregar; Muhammad Arifin Nasution (Journal of Education, Humaniora and Social Sciences (JEHSS), 2020)
The importance of entrepreneurship in society is not just to make improvements and changes in quality of life community, but also also proven to play a significant role in realizing the quality of the people and the nation. This study aims to determine the factors that determine the success of entrepreneurs in entrepreneurs in the city of Medan. This study uses quantitative research methods through the provision of questionnaires using predetermined indicator indicators in addition to extracting information through in-depth interviews. The results of the study show that lifestyle variables influence the success of an entrepreneur. In addition, lifestyle variables have a significant effect onsuccess variables entrepreneurial. So, the hypothesis is acceptable, namely the existence of partial lifestyle influences onsuccess intentions entrepreneurial. The results of partial tests explain that psychological capital variables (X2) have a positive effect. In addition, psychological capital variables have a significant effect onsuccess variables entrepreneurship. So, the hypothesis can be accepted, namely the influence of psychological capital partially onsuccess intentions. entrepreneurialThat individual talent variable (X3) has a positive effect and individual talent variables influencesuccess. entrepreneurIndividual talent variables have a significant effect onsuccess variables entrepreneurship. So, hypothesis 3 is acceptable, that is, the influence of individual talents partially on theintention to succeed  entrepreneur's.